Mapping the Interdisciplinary Landscape of Free Education Economics: A Bibliometric Analysis from 2015-2025 - Sarmiento, Allen Grace (Journal of Interdisciplinary Perspectives, 2025)
Research on the economics of free education is extensive but highly fragmented, making it difficult for scholars and policymakers to discern the field's intellectual structure. This study addresses this gap by providing the first comprehensive, quantitative overview of the research landscape. The objective was to identify foundational works, map primary research themes, and understand the relationships between different areas of study. Using bibliometric analysis of peer-reviewed articles from the Scopus database (2015–2025), the study employed co-citation analysis to map the field’s intellectual foundations and co-word analysis to identify its thematic structure. The results revealed eight distinct co-citation clusters, indicating that the field is an interdisciplinary domain drawing from econometrics, psychology, sociology, and political science, built upon foundational theories such as human capital. The co-word analysis identified three major thematic clusters focused on the socio-economic context, the human-centric evidence base, and public welfare outcomes. This study presents a comprehensive and objective framework for understanding the economics of free education, demonstrating that a holistic approach necessitates integrating multiple disciplinary perspectives beyond simple financial analysis to develop more effective and equitable educational policies.